2007
DOI: 10.1002/mc.20310
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of the oncogenic potential of β‐catenin by the subcellular distribution of plakoglobin

Abstract: Plakoglobin (Pg) and beta-catenin are homologous proteins that function in cell-cell adhesion and signaling. The cadherin-associated form of these proteins mediates adhesion, whereas the cytosolic/nuclear form has a signaling role. Despite their interactions with common cellular partners, beta-catenin has a well-documented oncogenic potential while Pg has a less characterized tumor suppressor activity. We showed previously that Pg overexpression in Pg-deficient SCC9 cells (SCC9-Pg-WT) induced Bcl-2 expression … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
49
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
4
2
1

Relationship

2
5

Authors

Journals

citations
Cited by 31 publications
(57 citation statements)
references
References 62 publications
8
49
0
Order By: Relevance
“…The colon carcinoma cell line SW620 was used because it expresses p53 and transcriptionally active b-catenin (Lamy et al, 2010;El-Bahrawy et al, 2004;Li et al, 2007). In agreement with the coimmunoprecipitation data, we did not observe an association between the 14-3-3s gene promoter and b-catenin in any cell line (Fig.…”
Section: Plakoglobin and P53 Interact In Both The Cytoplasm And Nucleussupporting
confidence: 85%
See 1 more Smart Citation
“…The colon carcinoma cell line SW620 was used because it expresses p53 and transcriptionally active b-catenin (Lamy et al, 2010;El-Bahrawy et al, 2004;Li et al, 2007). In agreement with the coimmunoprecipitation data, we did not observe an association between the 14-3-3s gene promoter and b-catenin in any cell line (Fig.…”
Section: Plakoglobin and P53 Interact In Both The Cytoplasm And Nucleussupporting
confidence: 85%
“…We chose to focus on 14-3-3s because (a) its mRNA levels were increased over 30-fold in SCC9-PG cells, one of the most notable increases in any of the identified p53-target genes, (b) it is a welldocumented tumor and metastasis suppressor (Lodygin and Hermeking, 2006;Lee and Lozano, 2006;Yi et al, 2009), (c) members of the 14-3-3 family are known to interact with a wide range of cellular partners and regulate several biological processes (Obsilová et al, 2008;Morrison, 2009; van Heusden, 2009), (d) 14-3-3s itself has been shown to interact with plakophilin, a component of the desmosomal plaque, which also contains plakoglobin (Benzinger et al, 2005) and (e) more recently it has been shown that various 14-3-3 proteins can regulate the Wnt pathway and b-catenin signaling , functionally linking these proteins to catenin proteins. Furthermore, we and others have shown that plakoglobin also regulates b-catenin subcellular localization and in turn its transcriptional activity (Salomon et al, 1997;Klymkowsky et al, 1999;Zhurinsky et al, 2000a;Li et al, 2007), thereby suggesting that both plakoglobin and 14-3-3s act to regulate the Wnt signaling pathway in similar, albeit not identical ways.…”
Section: Discussionmentioning
confidence: 69%
“…plakoglobin can modulate the amount of b-catenin and its signaling function in a cell context-dependent manner (Li et al, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…We then asked whether a-catenin could be a bridge between Nm23 and plakoglobin-Ncadherin complexes. To clarify this point, we assessed the interactions between Nm23, plakoglobin and Ncadherin in SCC9 cells expressing Flag-tagged wild-type plakoglobin or a mutant plakoglobin with a deletion in the N-terminal a-catenin binding domain (Pg-DN123; Li et al, 2007;Kolligs et al, 2000). Soluble and insoluble cell extracts from Pg-Flag and Pg-DN123 transfectants were processed for sequential immunoprecipitation and immunoblotting with Flag and Nm23 antibodies, respectively.…”
Section: Nm23 Interacts With A-cateninmentioning
confidence: 99%
See 1 more Smart Citation